Communities and ecosystems : linking the aboveground and belowground components - Wardle, David A., 1963- (Princeton, N.J. : Princeton University Press, 2002)
Most of the earth's terrestrial species live in the soil. These organisms, which include many thousands of species of fungi and nematodes, shape aboveground plant and animal life as well as our climate and atmosphere. Indeed, all terrestrial ecosystems consist of interdependent aboveground and belowground compartments. Despite this, aboveground and belowground ecology have been conducted largely in isolation. This book represents the first major synthesis to focus explicitly on the connections between aboveground and belowground subsystems--and their importance for community structure and e.
5. Completing the circle : how soil food web effects are manifested aboveground -- The decomposer food web -- Nitrogen transformations -- Microbial associates of plant roots -- Root herbivores -- Physical effects of soil biota -- Soil biota effects on aboveground food webs -- Synthesis -- 6. The regulation and function of biological diversity -- Assessment of soil diversity -- Stress and disturbance as controls of soil diversity -- Biotic controls of diversity -- The enigma of soil diversity -- Diversity of soil organisms over larger spatial scales -- Biodiversity and ecosystem function -- Synthesis -- 7. Global change phenomena in an aboveground-belowground context -- Species losses and gains -- Land use changes -- Carbon dioxide enrichment and nitrogen deposition -- Global climate change -- Synthesis -- 8. Underlying themes -- References -- Index.
Includes bibliographical references (pages 309-386).
Print version record.
In English.
JSTOR
Keywords: Soil ecology; Food chains (Ecology); Soil; Food Chain; Écologie du sol; Chaînes alimentaires (Écologie); NATURE -- Ecology; NATURE -- Ecosystems & Habitats -- Wilderness; SCIENCE -- Environmental Science; SCIENCE -- Life Sciences -- Ecology; SCIENCE -- Life Sciences -- Biology; Food chains (Ecology); Soil ecology; Bodenökologie; Nahrungskette; Ecosystemen; Biosfeer